Prototipe Battery Management System dengan mempertimbangkan State of Charge dan State of Health (Jurnal Perkeretaapian Indonesia (Indonesian Railway Journal), 2023)
The increasing importance of the battery used in everyday life, as well as to maintain the quality and reliability of the battery, makes a Battery Management System (BMS) indispensable. BMS can be used to avoid overcharging, short circuits, and extreme temperatures on batteries. The purpose of designing this BMS prototype is to monitor the SOC and SOH values of the battery in real-time. The SOC value is calculated using the Open Circuit Voltage (OCV) method and the Columb Counting (CC) method. Meanwhile, the SOH value is calculated by comparing the current load and the new condition load. In the BMS prototype, the voltage divider sensor, current sensor, and temperature sensor are connected to the battery. Data from the three sensors will be processed by Arduino and sent to the LabView software. LabView will display the battery's voltage, current, temperature, SOC, and SOH values. From the test results using old and new batteries, the BMS sensor components function with high accuracy. New batteries have better charge and discharge performance than old batteries. Old batteries also have a hotter temperature than new batteries. Therefore, BMS is needed to maintain the condition of the battery so that it works properly.